Exploring Housing Governance in Malaysia - Teng Teoh, Chai; Lateef Olanrewaju, Abdul; Yeow Tan, Seong (International Journal of Engineering and Technology, 2018)
Malaysia, in this era of increasing globalisation and rapid pace of urbanisation coupled with socioeconomic inefficiency, is suffering from severe housing problems – most notably affordable housing crisis. Though several prescribed measures in terms of incentives, policies and schemes attempting to alleviate the affordable housing crisis has been implemented, so far the result has proven to be insignificant. With the housing industry today becoming ever more complex, fragmented and involved by an ever increasing number of heterogeneous stakeholders, thereby it is not applicable for the government to have a one-sided decision making power on housing and other related policies. As such, the ‘governance’ approach, which ably brings together both public and private housing stakeholders into a collective body of decision-making and actions, has been deemed as a prerequisite for dealing with the Malaysian housing dilemma. There has been much discussion about bringing governance into urban development, land delivery, construction projects or other related services to bring about positive effects. However, the housing industry in Malaysia, particularly in the affordable segment, has not adopted this approach to the same extent. In order to remedy this issue, this study aims to develop housing governance for the Malaysian affordable housing industry. This paper reports part of the study in achieving the mentioned aim by literature reviewing factors involved that negatively influence the Malaysian affordable housing delivery. It was identified that there are 65 indicators, classified into financial factors, policy and regulatory factors, administrative factors and knowledge factors that constrains the Malaysia affordable housing delivery.